Assessment of the image quality of extended depth-of-focus intraocular lens models in polychromatic light - Lee, Yumi; Łabuz, Grzegorz; Son, Hyeck Soo; Yildirim, Timur Mert; Khoramnia, Ramin; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2020)
The use of monochromatic light in the assessment of intraocular lenses (IOLs) has been criticized for not representing the real-world situation. This study aimed to measure and compare the image quality of 3 extended depth-of-focus (EDOF) IOL models in monochromatic and polychromatic light.
Gesehen am 31.03.2020